Environmental policy stringency and firm efficiency in developing countries - Bao We Wal Bambe; Jean-Louis Combes; Ben-Vieira Kouassi; Sonia Schwartz (Small Business Economics, 2025)
This article examines the impact of environmental stringency on firm efficiency, using a large cross-country dataset of 68 developing countries from 2006–2020. We combine the newly published Environmental Performance Index (EPI) as an indicator of the stringency of environmental regulations with firm data from the World Bank Enterprise Surveys (WBES). Our results indicate that stricter environmental policies significantly increase firm efficiency, and the effect is robust. Moreover, we find that the intensity of environmental stringency matters, and that firm size, firm pollution intensity, and institutional quality also influence the relationship between environmental stringency and efficiency. Thus, our results support the Porter hypothesis in the case of developing countries.
Keywords: D21; D24; Q55; Q58; 330; Environmental policy stringency; Firm efficiency; Developing countries; Porter hypothesis